PENERAPAN METODE BERMAIN PERAN DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SDN 123 BANGKO - Marlina; Badaruddin Kaddas; Supriadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students at SDN 123 Bangko, especially in the learning process that is still teacher-centered and less varied. This study aims to determine the effect of the role-playing method in improving student learning outcomes at SDN 123 Bangko. The method used in this research is Classroom Action Research (CAR) which refers to the Kemmis and McTaggart model, consisting of two cycles with four stages: planning, implementation, observation, and reflection. The subjects of this study were 17 grade V students at SDN 123 Bangko, consisting of 10 male students and 7 female students. Data collection techniques used observation sheets, learning outcome tests, and documentation. The results showed that the application of the role-playing method could improve student learning outcomes. In the pre-cycle, the average student learning outcome was 55.3 with a classical completeness of 29.4%. After the implementation of Cycle I, the average increased to 68.2 with a classical completeness of 58.8%, and in Cycle II it increased to 81.5 with a classical completeness of 88.2%. Thus, it can be concluded that the role-playing method has a positive effect on improving student learning outcomes at SDN 123 Bangko.